Lithium-sulfur battery diaphragm with porous carbon-based composite material coating and preparation method of lithium-sulfur battery diaphragm
By applying a porous carbon-based composite coating on the lithium-sulfur battery separator, the chemical and physical adsorption effect of CDC@TiO2 is used to solve the problems of low ionic conductivity and intermediate product shuttle in lithium-sulfur batteries, and the cycle stability and capacity retention rate of the battery are significantly improved.
Patent Information
- Application Number
- CN202510010234.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Lithium-sulfur batteries face problems such as low ionic conductivity, serious shuttle phenomenon of intermediate products, and expansion of sulfur volume during charging and discharging, resulting in low sulfur utilization, serious self-discharge and poor cycle stability.
A lithium-sulfur battery separator coated with porous carbon-based composite material contains CDC@TiO2 and polyvinylidene fluoride (PVDF). Through the synergistic effect of chemical adsorption and physical adsorption of CDC@TiO2, the intermediate product diffusion is prevented and the lithium ion transmission channel is improved.
The liquid absorption, retention rate and ionic conductivity of lithium sulfur batteries are significantly improved, the cycle stability of the battery is extended, and a high capacity retention rate is maintained at a current density of 0.2C.
Smart Images

Figure CN119812673A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium-sulfur battery separator coated with a porous carbon-based composite material and a preparation method thereof. Background Art
[0002] The rapid growth of global energy demand has driven the development of next-generation high-energy-density rechargeable batteries. Among them, lithium-sulfur (Li-S) batteries have become a future battery technology that has attracted much attention due to their superior specific capacity and high theoretical energy density. However, Li-S batteries still face some challenges, such as low ionic conductivity, intermediate products (Li 2 S 6 and Li 2 S 4 ) and the volume expansion of sulfur during charge and discharge, which leads to low sulfur utilization, serious self-discharge problems and poor cycle stability.
[0003] Therefore, how to improve ionic conductivity, liquid absorption and retention rate, and improve cycle stability are still worthy of attention. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a lithium-sulfur battery separator coated with a porous carbon-based composite material.
[0005] Another object of the present invention is to provide a method for preparing the lithium-sulfur battery separator coated with the porous carbon-based composite material.
[0006] Another object of the present invention is to provide a slurry.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A lithium-sulfur battery separator coated with a porous carbon-based composite material, comprising: a base film and a coating on the base film, wherein the coating comprises: CDC@TiO 2 and polyvinylidene fluoride (PVDF), by weight, CDC@TiO 2 and polyvinylidene fluoride (PVDF) in a ratio of (25-36): (5-9), the CDC@TiO 2 The porous carbide-derived carbon (CDC) and titanium dioxide supported on the porous carbide-derived carbon (CDC).
[0009] In the above technical solution, by weight, CDC@TiO 2 The ratio of polyvinylidene fluoride (PVDF) is preferably (28 to 32): (5.5 to 6.5).
[0010] In the above technical scheme, CDC@TiO2 The method comprises: mixing tetrabutyl titanate, ethanol and porous carbide-derived carbon, stirring until uniform, and then standing at 60-70°C for 2-3 hours, and annealing at 600-800°C for 2-4 hours in an inert gas atmosphere to obtain CDC@TiO 2 , by mass, the ratio of porous carbide-derived carbon to tetrabutyl titanate is (20-30):(50-60).
[0011] In the above technical solution, the ratio of porous carbide-derived carbon to tetrabutyl titanate is preferably (22-28):(55-60) by mass.
[0012] In the preparation of CDC@TiO 2 In the method, the ratio of porous carbide-derived carbon to ethanol is (20-30): (10-20) by mass.
[0013] In the preparation of CDC@TiO 2 In the method, the ratio of porous carbide-derived carbon to ethanol is preferably (22-28):(10-18) by mass.
[0014] In the preparation of CDC@TiO 2 In the method, tetrabutyl titanate, ethanol and porous carbide derived carbon are mixed and stirred at room temperature until uniform. The stirring speed is 500-1000 rpm and the stirring time is 30-60 minutes.
[0015] In the above technical solution, the particle size of the porous carbide-derived carbon is D50=0.1-0.3 μm, D90=0.4-0.8 μm, and the specific surface area is 2000-2500 m 2 / g, and the porosity is 40-50%.
[0016] In the above technical solution, the porous carbide-derived carbon is a skeleton carbon structure remaining after the titanium atoms in titanium carbide are removed under the action of chlorine etching.
[0017] In the above technical solution, the method for preparing porous carbide-derived carbon comprises: treating a micron-sized metal carbide at T°C (15-20°C min -1 The porous carbide-derived carbon precursor is annealed at 550-650° C. for 1-2 h in a reducing atmosphere to remove residual chloride on the surface and inside the pores to obtain porous carbide-derived carbon (CDC), T=900-1000.
[0018] In the method for preparing porous carbide-derived carbon, the micron-sized metal carbide is titanium carbide powder.
[0019] In the method for preparing porous carbide-derived carbon, the micron-sized metal carbide is heated to the T°C in a nitrogen or inert gas atmosphere, and when the temperature reaches T°C, the nitrogen or inert gas is stopped and chlorine is replaced to perform the chlorine etching, and the flow rate of the chlorine is 30-40 mL / min. The method for preparing the porous carbon-based composite material coating lithium-sulfur battery separator comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining a porous carbon-based composite material coating lithium-sulfur battery separator.
[0020] In the above technical solution, the coating thickness is 2 to 3 μm.
[0021] In the above technical solution, the coating speed is 10 to 20 m / min.
[0022] A slurry, comprising: CDC@TiO 2 , polyvinylidene fluoride (PVDF) and solvent, by weight, CDC@TiO 2 , polyvinylidene fluoride (PVDF) and solvent in a ratio of (25-36): (5-9): (50-70), the CDC@TiO 2 The invention comprises porous carbide-derived carbon (CDC) and titanium dioxide supported on the porous carbide-derived carbon (CDC).
[0023] In the above technical solution, by weight, CDC@TiO 2 The ratio of polyvinylidene fluoride (PVDF) to the solvent is preferably (28 to 32): (5.5 to 6.5): (60 to 65).
[0024] In the above technical solution, the solvent is N-methylpyrrolidone (NMP).
[0025] The method for preparing the slurry comprises: 2 , polyvinylidene fluoride (PVDF) and a solvent are mixed until uniform to obtain a slurry.
[0026] The method for preparing the above slurry comprises the following steps:
[0027] Step 1, mixing a solvent and polyvinylidene fluoride (PVDF), and stirring until uniform to obtain a first solution;
[0028] In step 1, the stirring rotation speed is 2000-3000 r / min, the revolution speed is 50-70 r / min, and the stirring time is 30-40 min.
[0029] Step 2: Mix the first solution and CDC@TiO 2The mixture is mixed, and ultrasonically and stirred simultaneously under a vacuum environment until the mixture is uniformly mixed to obtain a slurry.
[0030] In step 2, in a vacuum environment, ultrasound and stirring are performed simultaneously for 30 to 40 minutes until the mixture is uniformly mixed, wherein the stirring rotation speed is 2000 to 3000 r / min, the revolution speed is 40 to 50 r / min, the ultrasonic frequency is 5 to 8 kHz, and the vacuum degree of the vacuum environment is 0.06 to 0.08 KPA.
[0031] CDC@TiO 2 Application in improving the liquid absorption rate, liquid retention rate and / or ion conductivity of lithium-sulfur battery separators.
[0032] CDC@TiO 2 Application in improving the capacity retention rate of lithium-sulfur batteries.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1.TiO 2 It has suitable potential barrier and stability and is environmentally friendly. It can chemically adsorb lithium polysulfide (LiPSs), inhibit LiPSs shuttle, and facilitate the transport of lithium ions. 2 The synergistic effect of chemical adsorption greatly blocks the intermediate products (Li 2 S 6 and Li 2 S 4 ) diffusion, inhibiting the shuttle effect of LiPSs. It not only provides a fast lithium ion transmission channel, but also prevents the diffusion of lithium polysulfide (LiPSs), thereby improving the cycle stability of the battery.
[0035] 2. The diaphragm of the present invention has a high liquid absorption rate, liquid retention rate and ion conductivity. The Li-S battery self-assembled from the diaphragm of the present invention has a high capacity retention rate at a current density of 0.2C. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 XRD of the porous carbide-derived carbon (CDC) obtained in Example 1;
[0037] Figure 2 CDC@TiO obtained in Example 1 2 TEM. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0039] Titanium carbide powder: Shanghai Shuitian Material Technology Co., Ltd.;
[0040] Tetrabutyl titanate: Sinopharm Chemical Reagent Co., Ltd.
[0041] Double planetary mixer: XFZH-30L.
[0042] In the following embodiments, the base film is a PE film, and the thickness of the base film is 7 microns.
[0043] High ionic conductivity: A high ionic conductivity separator allows lithium ions to pass faster, significantly increasing the battery's charge and discharge rates. Fast lithium ion transmission not only helps reduce energy loss during the charge and discharge process, but also maintains a high capacity after multiple cycles. In addition, a high ionic conductivity separator can also reduce the internal resistance of the battery, thereby reducing safety risks caused by internal overheating.
[0044] The present invention uses titanium carbide to remove metal atoms under the action of chlorine etching, and the remaining carbon atoms are rearranged and combined to obtain porous carbide-derived carbon (CDC) with a porous structure. Then, tetrabutyl titanate is used as a raw material to obtain CDC@TiO 2 .
[0045] Example 1
[0046] A method for preparing a slurry comprises the following steps:
[0047] Step 1, mixing a solvent and polyvinylidene fluoride (PVDF) in a double planetary mixer, stirring for 30 minutes until uniform, to obtain a first solution, the stirring rotation speed is 3000 r / min, the revolution speed is 70 r / min, and the solvent is N-methylpyrrolidone (NMP);
[0048] Step 2: Add CDC@TiO to the first solution 2 In a vacuum environment, in a double planetary mixer with ultrasonic oscillation function, ultrasonic and stirring were performed for 40 minutes until the mixture was uniformly mixed to obtain a slurry, wherein the stirring rotation speed was 3000r / min, the revolution speed was 50r / min, the ultrasonic frequency was 5kHz, and the vacuum degree of the vacuum environment was 0.06KPA. By mass fraction, CDC@TiO 2 The ratio of PVDF to solvent is 25:5:70, CDC@TiO 2 The invention comprises porous carbide-derived carbon (CDC) and titanium dioxide supported on the porous carbide-derived carbon (CDC).
[0049] Preparation of CDC@TiO 2The method comprises: firstly mixing tetrabutyl titanate and ethanol until uniform, then adding porous carbide derived carbon (CDC), first stirring at a speed of 500 rpm at room temperature for 30 minutes until uniform, then standing at 70°C for 2 hours to remove ethanol, transferring to a quartz tube, and annealing at 600°C for 2 hours under an argon atmosphere to obtain CDC@TiO 2 , the ratio of porous carbide-derived carbon to tetrabutyl titanate is 20:60 by weight, and the ratio of porous carbide-derived carbon to ethanol is 20:20 by weight, wherein the method for preparing porous carbide-derived carbon comprises: transferring micron-sized metal carbide (micron-sized metal carbide is titanium carbide powder, 200-300 mesh) to a quartz tube furnace through graphite paper, evacuating to 0.01 KPA, introducing argon, and heating at 15 ° C min under argon atmosphere. -1 The temperature was raised at a rate of 1000°C. When the temperature reached 1000°C, the argon gas was stopped and chlorine gas was introduced for chlorine etching (the flow rate of the chlorine gas was 40 mL / min). The chlorine etching lasted for 120 min. The chlorine gas was stopped and argon gas was introduced again to expel the residual gas impurities. The product was cooled to room temperature under an argon atmosphere to obtain a porous carbide-derived carbon (CDC) precursor. The product was heated to 1000°C and chlorine gas was introduced for 120 min. The product was etched with chlorine gas at a rate of 1000°C. 2 ) atmosphere, the porous carbide-derived carbon (CDC) precursor was annealed at 600 ° C for 1 h to remove the chlorides remaining on the surface and inside the pores, and then ground to obtain a powdered porous carbide-derived carbon (CDC). The particle size of the porous carbide-derived carbon was D50 = 0.125 μm, D90 = 0.506 μm, and the specific surface area was 2367 m 2 / g, and the porosity is 44.6%.
[0050] Example 2
[0051] A method for preparing a slurry comprises the following steps:
[0052] Step 1, mixing a solvent and polyvinylidene fluoride (PVDF) in a double planetary mixer, stirring for 30 minutes until uniform, to obtain a first solution, the stirring rotation speed is 2000 r / min, the revolution speed is 50 r / min, and the solvent is N-methylpyrrolidone (NMP);
[0053] Step 2: Add CDC@TiO to the first solution 2 In a vacuum environment, in a double planetary mixer with ultrasonic oscillation function, ultrasonic and stirring were performed for 30 minutes until the mixture was uniformly mixed to obtain a slurry, wherein the stirring rotation speed was 2500r / min, the revolution speed was 40r / min, the ultrasonic frequency was 5kHz, and the vacuum degree of the vacuum environment was 0.06KPA. By mass fraction, CDC@TiO 2The ratio of PVDF to solvent is 30:6:64, CDC@TiO 2 The invention comprises porous carbide-derived carbon (CDC) and titanium dioxide supported on the porous carbide-derived carbon (CDC).
[0054] Preparation of CDC@TiO 2 The method comprises: firstly mixing tetrabutyl titanate and ethanol until uniform, then adding porous carbide derived carbon (CDC), first stirring at 800 rpm at room temperature for 45 min until uniform, then standing at 70 ° C for 2 h to remove ethanol, transferring to a quartz tube, and annealing at 600 ° C for 2 h in an argon atmosphere to obtain CDC@TiO 2 , the ratio of porous carbide-derived carbon to tetrabutyl titanate is 25:60 by weight, and the ratio of porous carbide-derived carbon to ethanol is 25:15 by weight, wherein the method for preparing porous carbide-derived carbon comprises: transferring micron-sized metal carbide (micron-sized metal carbide is titanium carbide powder, 200-300 mesh) to a quartz tube furnace through graphite paper, evacuating to 0.02KPA, introducing argon, and heating at 15℃min under argon atmosphere. -1 The temperature was raised at a rate of 100 °C. When the temperature reached 900 °C, the argon gas was stopped and chlorine gas was introduced for chlorine etching (the flow rate of the chlorine gas was 40 mL / min). The chlorine etching was performed for 100 min. The chlorine gas was stopped and argon gas was introduced again to expel the residual gas impurities. The mixture was cooled to room temperature under an argon atmosphere to obtain a porous carbide-derived carbon (CDC) precursor. The CDC precursor was heated to 100 °C under a hydrogen (H 2 ) atmosphere, the porous carbide-derived carbon (CDC) precursor was annealed at 550 ° C for 1 h to remove the chlorides remaining on the surface and inside the pores, and then ground to obtain a powdered porous carbide-derived carbon (CDC). The particle size of the porous carbide-derived carbon was D50 = 0.205 μm, D90 = 0.496 μm, and the specific surface area was 2307 m 2 / g, and the porosity is 43.8%.
[0055] Example 3
[0056] A method for preparing a slurry comprises the following steps:
[0057] Step 1, mixing a solvent and polyvinylidene fluoride (PVDF) in a double planetary mixer, stirring for 35 minutes until uniform, to obtain a first solution, the stirring rotation speed is 2800 r / min, the revolution speed is 60 r / min, and the solvent is N-methylpyrrolidone (NMP);
[0058] Step 2: Add CDC@TiO to the first solution 2In a vacuum environment, in a double planetary mixer with ultrasonic oscillation function, ultrasonic and stirring were performed for 35 minutes until the mixture was uniformly mixed to obtain a slurry, wherein the stirring rotation speed was 2000r / min, the revolution speed was 40r / min, the ultrasonic frequency was 5kHz, and the vacuum degree of the vacuum environment was 0.06KPA. By mass fraction, CDC@TiO 2 The ratio of PVDF to solvent is 36:9:55, and CDC@TiO 2 The invention comprises porous carbide-derived carbon (CDC) and titanium dioxide supported on the porous carbide-derived carbon (CDC).
[0059] Preparation of CDC@TiO 2 The method comprises: firstly mixing tetrabutyl titanate and ethanol until uniform, then adding porous carbide derived carbon (CDC), first stirring at a speed of 1000 rpm at room temperature for 60 minutes until uniform, then standing at 70°C for 2 hours to remove ethanol, transferring to a quartz tube, and annealing at 600°C for 2 hours under an argon atmosphere to obtain CDC@TiO 2 , the ratio of porous carbide-derived carbon to tetrabutyl titanate is 30:50 by weight, and the ratio of porous carbide-derived carbon to ethanol is 30:20 by weight, wherein the method for preparing porous carbide-derived carbon comprises: transferring micron-sized metal carbide (micron-sized metal carbide is titanium carbide powder, 200-300 mesh) to a quartz tube furnace through graphite paper, evacuating to 0.03KPA, introducing argon, and heating at 15℃min under argon atmosphere. -1 The temperature was raised at a rate of 100 °C. When the temperature reached 950 °C, the argon gas was stopped and chlorine gas was introduced for chlorine etching (the flow rate of the chlorine gas was 40 mL / min). The chlorine etching lasted for 110 min. The chlorine gas was stopped and argon gas was introduced again to expel the residual gas impurities. The product was cooled to room temperature under an argon atmosphere to obtain a porous carbide-derived carbon (CDC) precursor. The product was heated to 950 °C and chlorine gas was introduced for 110 min. The product was etched with hydrogen (H 2 ) atmosphere, the porous carbide-derived carbon (CDC) precursor was annealed at 650 ° C for 1.5 h to remove the chlorides remaining on the surface and inside the pores, and then ground to obtain a powdered porous carbide-derived carbon (CDC). The particle size of the porous carbide-derived carbon was D50 = 0.189 μm, D90 = 0.566 μm, and the specific surface area was 2297 m 2 / g, and the porosity is 45.2%.
[0060] Comparative Example 1
[0061] A method for preparing a slurry comprises the following steps:
[0062] Step 1, mixing N-methylpyrrolidone (NMP) and PVDF in a double planetary mixer, stirring for 30 minutes until uniform, to obtain solution A, wherein the stirring rotation speed is 2700 r / min and the revolution speed is 55 r / min;
[0063] Step 2, add the porous carbide-derived carbon (CDC) prepared in Example 1 to solution A, and in a vacuum environment, in a double planetary mixer with an ultrasonic oscillation function, simultaneously ultrasonicate and stir for 35 minutes until the mixture is uniformly mixed to obtain a slurry, wherein the stirring rotation speed is 2000r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 5kHz, the vacuum degree of the vacuum environment is 0.06KPA, and the ratio of porous carbide-derived carbon (CDC), PVDF and NMP is 30:5:65 by mass.
[0064] Comparative Example 2
[0065] A method for preparing a slurry is substantially the same as that of Comparative Example 1, except that "porous carbide-derived carbon (CDC)" is replaced with "titanium carbide powder". The mesh size of the titanium carbide powder is 200-300 mesh.
[0066] Examples 4 to 6 and Comparative Examples 3 to 4
[0067] A preparation method of a lithium-sulfur battery, comprising: packaging a positive electrode, a negative electrode, an electrolyte and a separator to obtain a soft-pack battery with an area of 10 cm×10 cm and a thickness of 3 mm, wherein the positive electrode material in the positive electrode is lithium iron phosphate (powder), the negative electrode material in the negative electrode is graphite, the electrolyte is a mixture of an electrolyte and a solvent, and the electrolyte is lithium hexafluorophosphate (LiPF 6 ), the solvent is a mixture of ethylene carbonate and dimethyl carbonate, the concentration of the electrolyte in the electrolyte is 1.0M, and the ratio of ethylene carbonate to dimethyl carbonate is 1:1 by volume. The preparation method of the diaphragm comprises: placing a base film on a coating machine equipped with slurry, coating the slurry on one side of the base film at a speed of 20m / min, pulling it into a drying device through a pulling roller, drying it at 60°C for 3min, obtaining a coating on the base film, and obtaining a diaphragm. The slurry is one of Examples 1 to 3 and Comparative Examples 1 to 2.
[0068] Table 1
[0069] Lithium-sulfur battery Slurry for preparing diaphragm Example 4 Example 1 Example 5 Example 2 Example 6 Example 3 Comparative Example 3 Comparative Example 1 Comparative Example 4 Comparative Example 2
[0070] The parameters of the diaphragm prepared from the slurry of Example 1 are as follows:
[0071]
[0072] The parameters of the diaphragm prepared from the slurry of Example 2 are as follows:
[0073]
[0074] The parameters of the diaphragm prepared from the slurry of Example 3 are as follows:
[0075]
[0076]
[0077] The parameters of the diaphragm prepared from the slurry of Comparative Example 1 are as follows:
[0078]
[0079] The parameters of the diaphragm prepared from the slurry of Comparative Example 2 are as follows:
[0080]
[0081] At a current density of 0.2C, the capacity retention rate of the lithium-sulfur battery prepared in Example 4 after 100 cycles is 90.8%, the capacity retention rate of the lithium-sulfur battery prepared in Example 5 after 100 cycles is 92.3%, the capacity retention rate of the lithium-sulfur battery prepared in Example 6 after 100 cycles is 91.2%, the capacity retention rate of the lithium-sulfur battery prepared in Comparative Example 3 after 100 cycles is 70.2%, and the capacity retention rate of the lithium-sulfur battery prepared in Comparative Example 4 after 100 cycles is 60.5%.
[0082] Figure 1 XRD of porous carbide-derived carbon (CDC) obtained in Example 1, Figure 1 It can be seen that a broad diffuse peak appears between 20° and 23° in the XRD spectrum, representing the existence of a short-range ordered region inside the material, which is a typical diffraction peak of amorphous carbon. This proves that porous carbide-derived carbon (CDC) is successfully prepared.
[0083] Figure 2 CDC@TiO obtained in Example 1 2 TEM, by Figure 2 It can be seen that the porous carbide-derived carbon (CDC) is loaded with TiO 2 .
[0084] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A lithium-sulfur battery separator coated with a porous carbon-based composite material, characterized in that: include: The base film and the coating on the base film include: CDC@TiO2 and polyvinylidene fluoride, and the ratio of CDC@TiO2 to polyvinylidene fluoride is (25-36): (5-9) by mass. The CDC@TiO2 includes porous carbide-derived carbon and titanium dioxide loaded on the porous carbide-derived carbon.
2. The lithium-sulfur battery separator of the porous carbon-based composite material coating according to claim 1, characterized in that: The method for preparing CDC@TiO2 comprises: mixing tetrabutyl titanate, ethanol and porous carbide-derived carbon, stirring until uniform, and then standing at 60-70°C for 2-3 hours, and annealing at 600-800°C for 2-4 hours under an inert gas atmosphere to obtain CDC@TiO2, wherein the ratio of porous carbide-derived carbon to tetrabutyl titanate is (20-30) by weight: (50–60) The porous carbide-derived carbon is the skeletal carbon structure remaining after the titanium atoms in titanium carbide are removed under the action of chlorine etching.
3. The lithium-sulfur battery separator of the porous carbon-based composite material coating according to claim 2, characterized in that: The ratio of the porous carbide-derived carbon to the ethanol is (20-30):(10-20) by weight.
4. The lithium-sulfur battery separator of the porous carbon-based composite material coating according to claim 2, characterized in that: The particle size of porous carbide-derived carbon is D50 = 0.1 ~ 0.3 μm, D90 = 0.4 ~ 0.8 μm, and the specific surface area is 2000 ~ 2500 m 2 / g, and the porosity is 40-50%.
5. The method for preparing a lithium-sulfur battery separator coated with a porous carbon-based composite material according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on a base film and dried to obtain a coating on the base film, thereby obtaining a lithium-sulfur battery separator coated with a porous carbon-based composite material.
6. A slurry, characterized in that: include: CDC@TiO2, polyvinylidene fluoride and solvent, in terms of mass fractions, the ratio of CDC@TiO2, polyvinylidene fluoride and solvent is (25-36):(5-9):(50-70), and the CDC@TiO2 includes porous carbide-derived carbon and titanium dioxide supported on the porous carbide-derived carbon.
7. The slurry according to claim 6, characterized in that The solvent is N-methylpyrrolidone.
8. A method for preparing the slurry according to claim 6, comprising: CDC@TiO2, polyvinylidene fluoride and solvent are mixed until uniform to obtain a slurry.
9. Application of CDC@TiO2 in improving the liquid absorption rate, liquid retention rate and / or ionic conductivity of lithium-sulfur battery separators.
10. Application of CDC@TiO2 in improving the capacity retention rate of lithium-sulfur batteries.
Citation Information
Patent Citations
Composite diaphragm for lithium-selenium battery and preparation method of composite diaphragm
CN104638219A
Isolating layer used for lithium-sulfur battery
CN106935773A
Double-effect composite membrane used for lithium sulphur battery and preparation method thereof
CN108461694A
Durable lithium battery
CN115621525A
Battery with reference electrode for voltage monitoring
US20140375325A1